Anxiety, planning strategies, and the development of argumentation in academic writing - Lorna Bourke; Alan Yates (Educational Futures)
The study investigated the interaction between planning strategy (outline planning, mind mapping, no-plan) and level of trait anxiety in the development of argumentation, and linguistic coherence in academic texts written by undergraduate students. Low anxious students benefited more by generating a greater number of pro-and contra-arguments for a specified position in a debate when assigned to the outline planning condition.Whereas, students reporting high anxiety incorporated a wider diversity of connectives to bind the arguments in their essays when asked to plan with a mind map strategy.In addition, individual differences in anxiety were also instrumental in determining the benefits that could be gained from different types of planning strategy when the overall quality of elaboration of argumentation present in the plans and essays was assessed. Therefore, it is important to understand where the interaction of anxiety on different modes of organisation strategy is implicated before making recommendations for the most appropriate form of pre-writing instruction for students undertaking academic writing tasks.